2016
DOI: 10.2147/ijn.s101563
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of ropivacaine nanoparticles for sciatic nerve block on postoperative pain in rats

Abstract: Purpose The analgesic effect of ropivacaine (Rop) for nerve block lasts only ~3–6 hours for single use. The aim of this study was to develop long-acting regional anesthetic Rop nanoparticles and investigate the effects of sciatic nerve block on postoperative pain in rats. Materials and methods Rop nanoparticles were developed using polyethylene glycol-co-polylactic acid (PELA). One hundred and twenty adult male Wistar rats were randomly divided into four groups (n=30, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Studies speci cally designed to address this issue are required. Sustained-release local anesthetics have been reported to treat postoperative pain [5]. The liposomal bupivacaine injectable suspension (EXPAREL®; Pacira Pharmaceuticals, Inc., USA) has received FDA Approval for in ltration into a surgical site to provide postoperative analgesia in adults based on clinical trials in which subjects had undergone bunion reaction [29] and hemorrhoidectomy [30], demonstrating e cacy for 36 h and 72 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies speci cally designed to address this issue are required. Sustained-release local anesthetics have been reported to treat postoperative pain [5]. The liposomal bupivacaine injectable suspension (EXPAREL®; Pacira Pharmaceuticals, Inc., USA) has received FDA Approval for in ltration into a surgical site to provide postoperative analgesia in adults based on clinical trials in which subjects had undergone bunion reaction [29] and hemorrhoidectomy [30], demonstrating e cacy for 36 h and 72 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that 10-50% of patients undergoing surgery experience postoperative pain lasting more than 1 month, and 2-10% of these patients continue to experience moderate to severe chronic pain [3]. Although many new devices for postoperative pain have been developed, inadequate postoperative analgesia occurs because the anesthetic cannot meet the ondemand requirements [4][5][6]. Inadequate management of postoperative pain can lead to severe consequences, such as poor immediate postoperative effects, prolonged hospital stays, poor patient satisfaction, and increased burden on patients and health systems [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with solid lipid nanoparticles, silver nanoparticles, and liposomes have been shown to increase the anesthesia duration of drugs formulations, when compared to their respective plain solutions 35–37. As a widely used local anesthesia in clinics, the efficacy of RVC was preferred because of its reduced toxicity 38. Thus, we imagined the treatment of pain with long-acting RVC is exciting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that 10%–50% of patients undergoing surgery experience postoperative pain lasting more than 1 month, and 2%–10% of these patients continue to experience moderate to severe chronic pain ( Wang et al, 2020 ). Although many new devices for postoperative pain have been developed, inadequate postoperative analgesia occurs because the anesthetic cannot meet the on-demand requirements ( Tobe et al, 2010 ; Wang et al, 2016 ; Rwei et al, 2017 ; Chen et al, 2020 ). Inadequate management of postoperative pain can lead to severe consequences, such as poor immediate postoperative effects, prolonged hospital stays, poor patient satisfaction, and increased burden on patients and health systems ( Beaulieu, 2021 ; Joseph et al, 2021 ; Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%